The importance of forward flow and venous congestion in diuretic response in acute heart failure: Insights from the ESCAPE trial. (15th June 2023) - Eder, Maxwell; Griffin, Matthew; Moreno-Villagomez, Julieta; Bellumkonda, Lavanya; Maulion, Christopher; Asher, Jennifer; Wilson, Francis P.; Cox, Zachary L.; Ivey-Miranda, Juan B.; Rao, Veena S.; Butler, Javed; Borlaug, Barry A.; et al.
Abstract: Aims: Previous studies have suggested venous congestion as a stronger mediator of negative cardio-renal interactions than low cardiac output, with neither factor having a dominant role. While the influence of these parameters on glomerular filtration have been described, the impact on diuretic responsiveness is unclear. The goal of this analysis was to understand the hemodynamic correlates of diuretic response in hospitalized patients with heart failure. Methods and results: We analyzed patients from the Evaluation Study of Congestive Heart Failure and Pulmonary Artery Catheterization Effectiveness (ESCAPE) dataset. Diuretic efficiency (DE) was defined as the average daily net fluid output per doubling of the peak loop diuretic dose. We evaluated a pulmonary artery catheter hemodynamic-guided cohort ( n = 190) and a transthoracic echocardiogram (TTE) cohort ( n = 324) where DE was evaluated with hemodynamic and TTE parameters. Metrics of "forward flow" such as cardiac index, mean arterial pressure and left ventricular ejection fraction were not associated with DE ( p > 0.2 for all). Worse baseline venous congestion was paradoxically associated with better DE as assessed by right atrial pressure (RAP), right atrial area (RAA), and right ventricular systolic and diastolic area ( p < 0.05 for all). Renal perfusion pressure (capturing both congestion and forward flow) was not associated with diuretic response ( p = 0.84). Conclusions: Worse venous congestion was weakly associated with better loop diuretic response. Metrics of "forward flow" did not demonstrate any correlation with diuretic response. These observations raise questions about the concept of central hemodynamic perturbations as the primary drivers of diuretic resistance on a population level in HF. Highlights: Increased venous congestion weakly predicts better diuretic response. Metrics of forward flow do not correlate with diuretic response. Central hemodynamics do not appear to be a dominant driver of diuretic resistance.